1992
DOI: 10.1080/08858199209528186
|View full text |Cite
|
Sign up to set email alerts
|

Reaching special populations with breast and cervical cancer public education

Abstract: With passage of the Breast and Cervical Cancer Mortality Prevention Act of 1990, significant activity has emerged in the development, implementation, and evaluation of breast and cervical cancer screening programs targeting underserved populations. This activity has prompted health educators and program planners to identify barriers to breast and cervical cancer screening specific to low-income and minority women, those traditionally underserved by cancer control programs, and to develop strategies that addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…1995; Baker et al . 1997), breast and cervical screening services (Coyne et al . 1992; Lindau et al .…”
Section: Health Literacy: Its Consequencesmentioning
confidence: 99%
“…1995; Baker et al . 1997), breast and cervical screening services (Coyne et al . 1992; Lindau et al .…”
Section: Health Literacy: Its Consequencesmentioning
confidence: 99%
“…Studies have found that perceived susceptibility and severity are not associated with mammography screening (Holm, Frank, & Curtin, 1999;Maxwell et al, 1998;Thomas et al, 1996), although many studies have identifi ed perceived benefi ts to be positively associated (Choi, Park, & Han, 2001;Holm et al;Thomas et al) and perceived barriers to be negatively associated with mammography screening. Researchers have concluded that cost, time, lack of physician referrals, and concern about radiation exposure are barriers that signifi cantly affect mammography use (Coyne, Hohman, & Levinson, 1992;Maxwell et al, 1998).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This powerlessness may account for some of the anxiety associated with cancer. According previous evidences, a major barrier to cancer screening was culturally based embarrassment and similar emotions ( Coyne , 1992, Bakemeier et al, 1995, Stein , 1990. The inability to speak English fluently interferes with Hispanic women's ability to obtain important health information and to communicate with health professionals.…”
Section: Perceived Barriersmentioning
confidence: 99%